1994
DOI: 10.1111/j.1399-3038.1994.tb00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Cow's milk protein allergy and intolerance in infancy Some clinical, epidemiological and immunological aspects

Abstract: Reproducible clinically abnormal reactions to cow's milk protein (CMP) may be due to the interaction between one or more milk proteins and one or more immune mechanisms, possibly any of the four basic types of hypersensitivity reactions. At present, evidence for type I, III and IV reactions against CMP has been demonstrated. Immunologically mediated reactions, mainly immediate IgE‐mediated reactions are defined as cow's milk protein allergy (CMPA). Non immunologically reactions against CMP are defined as cow's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
144
3
15

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(165 citation statements)
references
References 242 publications
3
144
3
15
Order By: Relevance
“…Estes problemas, em escala muito maior, devem ser encontrados por muitos pediatras, pneumologistas e alergistas. Host, em 1994, afirmou que aproximadamente um terço dos casos sugestivos de alergia ao leite de vaca não são confirmados através de métodos adequados (9) . Em nosso estudo, 29,1% dos casos suspeitos não foram confirmados.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Estes problemas, em escala muito maior, devem ser encontrados por muitos pediatras, pneumologistas e alergistas. Host, em 1994, afirmou que aproximadamente um terço dos casos sugestivos de alergia ao leite de vaca não são confirmados através de métodos adequados (9) . Em nosso estudo, 29,1% dos casos suspeitos não foram confirmados.…”
Section: Resultsunclassified
“…Por sua vez, Host e Halken, em 1990 (29) , e Host, em 1994 (9) , observaram boa correlação entre resultados de estudos abertos em ambiente hospitalar e a exposição duplo-cega placebo-controlada. A exposição duplo-cega serviria para excluir a influência psicológica, de menor importância em crianças (30) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…[1][2][3][4][5] The natural history of cow's milk protein allergy (CMPA) described until the 2000s showed that allergy would develop early, with resolution in the first years of life. [6][7][8] More recently, Skripak et al 1 reported in 2007 that 21% of the children with CMPA remained allergic up to the age of 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…[2,4] After the age of 3 years, more than 70% of these children are expected to be free from allergic symptoms related to ingested foods, known as 'tolerance'. [4][5][6][7][8][9] After this time, they tend to develop further allergic diseases, including asthma, allergic rhinitis, and conjunctivitis with increased levels of serum IgE. This sequential development of allergic disease manifestations is often referred to as the 'atopic march'.…”
Section: Introductionmentioning
confidence: 99%